Examining dog-care facilities in Davao City using the five freedom of animal welfare as framework towards design guidelines for dog hotels - Agustin, Joseph Dave P. (2020)
Every day people face the question of what to do with their pets when travel, illness, or family emergencies disrupt normal care. Some pet owners attempt to solve this problem by taking their pets with them, only to discover that hotel restrictions, travel-induced pet illness, and runaway pets can turn their trip into a disaster. Other pet owners turn over the care of their animals to well-meaning but untrained neighbors or friends. Again, the results are often unsatisfactory. Pets entrusted to such part-time custodians frequently escape or become seriously ill because of lack of reliable, frequent, and knowledgeable supervision. This is where the dog hotel can be invaluable for anyone that really loves their canine family member. As with a quality children?s day care, a dog hotel isn?t just some place for your dog to kill time until you get home. A dog hotel can actually be a healthy, enriching experience that improves your dog?s quality of life in ways you might not be able to provide at all if you have a demanding schedule. This study mainly conducts an assessment of the insights of the pet owners towards having a dog hotel as a one stop facility is a good basis for formulating a design guideline for a dog hotel that provides the basic services needed by the dogs when their owners travel, have illness, or family emergencies that disrupt provision of normal care to the dogs. The study will use a researcher made survey instrument and guide question in the data gathering of the study. It is composed of 3 parts which are the characteristics of the common breeds, size, and behavioral traits of canines in Davao City followed by statements about existing conditions of care given to dogs then lastly statements about acceptability of the dog hotel being constructed in Davao City. Using the data acquired from the questionnaires, the researcher identified that dog breeds and sizes play a very important role in finding out what are the spaces (physical comfort) needed or required for the said project. For example, the area for the kennel would vary depending on the height and weight of the canine to be housed. Food and water consumption is computed depending on the breed and size of the dog to prevent underfeeding and overfeeding. The amount of play time and walking needed to ensure that they get tired. With the data collected, the researcher concluded that a lot of factors, Nourishment Practices, Environmental Enrichment Practices, Animal Health Practices, Social Experience Practices, and Control Over Self and Environment Practices have an effect on the overall welfare of our furry companion. It is important to check if our normal standard of care is on par with the humane treatment what our pets truly deserve."